THE EFFECT OF TAX AWARENESS, TAX SOCIALIZATION, TAX SANCTIONS AND SERVICE QUALITY ON MOTOR VEHICLES TAXPAYER COMPLIANCE (A Case Study at Kantor Bersama Samsat Karangploso) - Salindeho, Vika Awuri (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2020)
Indonesia’s state revenue mostly comes from the tax revenue sector. One of the local taxes that has a major role in receiving provincial government revenue is the motor vehicle tax. This research aimed to analyze the effect of tax awareness, tax socialization, tax sanctions, and service quality on motor vehicles taxpayer compliance, a case study at Kantor Bersama Samsat Karangploso. This research is quantitative, and the data was collected by survey method or questionnaire. The research data were analyzed using the Statistical Product and Service Solutions (SPSS). The samples were 100 taxpayers who paid motor vehicle tax at Kantor Bersama Samsat Karangploso. The results show that tax awareness and tax sanctions have positive and significant effect on taxpayer compliance to pay motor vehicle tax. Meanwhile, tax socialization and service quality have no significant effect on taxpayer compliance to pay motor vehicle tax.Keywords; motor vehicle tax compliance, tax awareness, tax socialization, tax sanctions, service quality.